Tilted Implants for Full-Arch Rehabilitations in Completely Edentulous Maxilla: A Retrospective Study - Nicolò Cavalli; Bruno Barbaro; Davide Spasari; Francesco Azzola; Alberto Ciatti; Luca Francetti (International Journal of Dentistry)
Purpose. The aims of this study were to assess the treatment outcome of immediately loaded full-arch fixed bridges anchored to both tilted and axially placed implants in the edentulous maxilla and to evaluate the incidence of biological and prosthetic complications. Materials and Methods. Thirty-four patients (18 women and 16 men) were included in the study. Each patient received a maxillary full-arch fixed bridge supported by two axial implants and two distal tilted implants. A total of 136 implants were inserted. Loading was applied within 48 hours of surgery and definitive restorations were placed 4 to 6 months later. Patients were scheduled for followup at 6, 12, 18, and 24 months and annually up to 5 years. At each followup plaque level and bleeding scores were assessed and every complication was recorded. Results. The overall follow-up range was 12 to 73 months (mean 38.8 months). No implant failures were recorded to date, leading to a cumulative implant survival rate of 100%. Biological complications were recorded such as alveolar mucositis (11.8% patients), peri-implantitis (5.9% patients), and temporomandibular joint pain (5.9% patients). The most common prosthetic complications were the fracture or detachment of one or multiple acrylic teeth in both the temporary (20.6% patients) and definitive (17.7% patients) prosthesis and the minor acrylic fractures in the temporary (14.7% patients) and definitive (2.9% patients) prosthesis. Hygienic complications occurred in 38.2% patients. No patients’ dissatisfactions were recorded. Conclusions. The high cumulative implant survival rate indicates that this technique could be considered a viable treatment option. An effective recall program is important to early intercept and correct prosthetic and biologic complications in order to avoid implant and prosthetic failures.